A Philological Study of Texts in Connection with Aṯtrt and Aṯirat in the Ugaritic Language - Beyers Brink, Marthinus (1977)
Thesis presented for the degree of Doctor in Literature (Semitic Languages) at the University of Stellenbosch, September